The Social Construction of Addiction and Sexual Deviancy: A Comparative Analysis of the Experts in Policy Debate - O'Brien, Haillie (Université d'Ottawa / University of Ottawa, 2017)
Sexual deviancy and addiction are two concepts that have undergone considerable development in the way in which they are constructed. Since the 1800s both concepts have come to the attention of the medical field, psychological field and the criminal justice system which have made numerous attempts to regulate and treat them within these realms. By using the lens of social construction and Spector and Kitsuse’s theory of social problems, this project explores how experts describe sexual deviancy and addiction. Important considerations involving the significance of victims and a victim status emerge from the analysis, as the differentiating factors between demands for treatment for addiction, while sexual deviancy experiences an increasingly punitive regime.
Keywords: Social Construction; Addiction; Sexual Deviancy; Sexual Offending; Spector and Kitsuse; Social Problems